Implementing Pre‐Emptive Pharmacogenetics: Impact of Early Pharmacogenetic Screening in a Pediatric Oncology Cohort of 1,151 Subjects - Bernsen, Emma C.; Verwiel, Eugène T.P.; Lee, Maaike; Swen, Jesse J.; Santoso, Marcel; Brigitha, Leiah J.; Admiraal, Rick; Tops, Bastiaan B.J.; Huitema, Alwin D.R.; Kemmeren, Patrick; Hehir‐Kwa, Jayne Y.; Hanff, Lidwien M.; et al. (Clinical pharmacology and therapeutics, 2025)
In pediatric oncology, pharmacogenetic guidelines are underutilized and the potential impact of pre‐emptive pharmacogenetic screening remains largely unexplored despite this field's need for individualized approaches. While comprehensive pharmacogenetic guidelines are not yet available for all anticancer drugs, evidence‐based recommendations exist for a subset of supportive care drugs and anticancer drugs, including thiopurines, irinotecan, capecitabine, and 5‐fluorouracil. In this study, we evaluate the potential impact of pre‐emptive pharmacogenetic screening by retrospectively identifying opportunities for dose or treatment adjustments within a national pediatric oncology cohort. Our analysis focused on ten genes and 28 drugs relevant to pediatric oncology, which are included in the Clinical Pharmacogenetics Implementation Consortium and the Dutch Pharmacogenetics Working Group guidelines. In a cohort of 1,151 pediatric oncology subjects, we identified that 16% of individuals could have benefited from altered drug dosing or treatment. These include dose and treatment recommendations for allopurinol, nonsteroidal anti‐inflammatory drugs, phenytoin, amitriptyline, proton pump inhibitors, voriconazole, tramadol, codeine, paroxetine, tacrolimus, rasburicase, and 6‐mercaptopurine. As genetic data increasingly becomes available through molecular diagnostics in pediatric oncology, there is a unique opportunity to re‐utilize this data for pre‐emptive pharmacogenetic screening. Leveraging genetic profiles to guide clinicians in drug selection and dose optimization can improve patient outcomes by enhancing the safety and efficacy of treatments. We therefore recommend incorporating pharmacogenetic screening into clinical workflows to advance personalized medicine in pediatric oncology.